An annotated distributional checklist of Vespidae (Hymenoptera: Vespoidea) of India - Gawas, Sandesh M.; Kumar, P. Girish; Pannure, Arati; Gupta, Ankita; Carpenter, James M. (Zootaxa, 2020)
This study presents a checklist of the vespid wasps (Hymenoptera: Vespidae) of India. A total of 288 species belonging to 60 genera and 5 subfamilies of Vespidae are known to occur within the political boundaries of India. A complete list of species, comprising valid scientific names, synonyms, geographical distribution within and outside India, along with references, is provided. One new synonymy is proposed.